2021
DOI: 10.3892/etm.2021.10039
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thyroid carcinomas in an extended retrospective study of 526 autopsies

Abstract: Thyroid cancer accounts for 1% of all malignancies, and is becoming increasingly common worldwide. The literature reports a prevalence of ~50% of thyroid nodules detected during autopsies in subjects with unknown thyroid pathology. An extended retrospective study of 526 autopsy cases was performed to identify the prevalence of thyroid carcinoma, among various types of thyroid nodules identified incidentally. Tissue samples were taken from thyroid nodules, for investigation of the presence of thyroid carcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…de Noronha et al also disregarded the whole importance of gross examination of heart findings as most of the young sudden cardiac death patients showed grossly normal heart (45%), and only 10% exhibited coronary artery disease [36]. Mohorea et al were able to put their findings only based on microscopy as grossly, the thyroid glands were normal [37,38].…”
Section: Role Of Gross (Macroscopic) Examination In Autopsymentioning
confidence: 99%
“…de Noronha et al also disregarded the whole importance of gross examination of heart findings as most of the young sudden cardiac death patients showed grossly normal heart (45%), and only 10% exhibited coronary artery disease [36]. Mohorea et al were able to put their findings only based on microscopy as grossly, the thyroid glands were normal [37,38].…”
Section: Role Of Gross (Macroscopic) Examination In Autopsymentioning
confidence: 99%
“…The six largest studies regarding differentiation between benign and metastatic cervical lymp nodes, conducted between 2014 and 2019, show that CEUS has a good diagnostic accuracy superior to standard US and Color-Doppler grayscale alone [59,74,[77][78][79] (Table 1). 3 The study divides patients into two groups, PTC (>10mm), PTMC (<10mm); 4 The evaluation is based on a prediction model combining both the parameters obtained from the CEUS and clinical parameters. Furthermore, both Hong et al and Chen et al demonstrate how a combination of US and CEUS is more accurate on the whole than any of these two techniques used individually: the Hong et al paper reported a detected a B mode US + CEUS accuracy of 92.2% (vs. 89.3% of CEUS and 84.6% of grayscale US alone) [77]; the Chen et al paper reported a B mode US + CEUS accuracy of 92.7% (vs. 89.1% of CEUS and 80.0% of grayscale US alone) [79].…”
Section: Evaluation Of Lymph-node Local Staging Using Ceusmentioning
confidence: 99%
“…It is noteworthy that the incidence of the thyroid nodule increases significantly as well as that of the malignant rate. [ 3 ]. However, baseline US alone is not always effective to achieve thyroid nodule characterization; that is why, especially in recent years, the support of other imaging modalities have become increasingly necessary to limit as much as possible the use of Fine Needle Aspiration Biopsy/Cytology, Core biopsy or even the diagnostic thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…La presencia de nódulos tiroideos es muy frecuente, con una incidencia aproximada del 5% de nódulos detectables a la palpación, del 50% en las autopsias [14] y de hasta de 68% en la ecografía [15]. La ecografía de tiroides realizada por profesionales no radiólogos: abordaje sistemático de la exploración, realización e interpretación Alonso-Tores A; Monte-González JC; Castaño-Saiz AM et al…”
Section: B) El Nódulo Tiroideounclassified